PDE-5 Inhibitors in Scleroderma Raynaud Phenomenon and Digital Ulcers: Current Status of Clinical Trials. (2nd November 2011) - Impens, Ann J.; Phillips, Kristine; Schiopu, Elena
Abstract : Systemic sclerosis- (SSc-) related vasculopathy, as manifested by Raynaud's Phenomenon (RP) and digital ulcers (DUs), is associated with significant impairment of the quality of life and morbidity. The current vasoactive approach for SSc-RP, although employing vasodilators, is entirely off-label. PDE-5 inhibitors improve peripheral circulation, are well tolerated, and are widely used for various forms of constrictive vasculopathies. This class of medications has become one of the first lines of treatment of SSc-RP and SSc-DUs among rheumatologists that routinely treat SSc patients. Due to the lack of robust randomized clinical trials of PDE-5 inhibitors in SSc-RP/DUs, the PDE-5 inhibitors have not been FDA approved for these particular indications, which constitutes a significant barrier to prescribing this category of drugs. This paper reviews the current state of evidence-based knowledge in SSc-related vasculopathy and the use of PDE-5 inhibitors.